CCP encyclopedia of Philippine art - Cultural Center of the Philippines; Distributed Processing Systems, Inc. ([Manila] Cultural Center of the Philippines Distributed Processing Systems, 1998)
This is the CD-ROM version of the 10-volume encyclopedia first published in 1994. It contains the updated biographical entries of those who received the National Artist Awards and those who passed away since 1994. All other entries follow the cut-off date of 1992 set by the first edition. It also contains videoclips of Filipino films, theater and dance, and audio samples of Philippine music and musical instruments.
Disc 1. Peoples of the Philippines -- Philippine music -- Philippine dance -- Philippine literature -- Disc 2. Philippine architecture -- Philippine visual arts -- Philipine film -- Philippine theater.
Title from disc surface.
"Mac & PC"--Disc surface.
Also available in print format.
System requirements for Macintosh: Power PC; System 7.1 or higher; 16 MB RAM; QuickTime 2.1 or higher; 4-speed CD-ROM drive.
System requirements for PC: Windows 95; Pentium processor; 16 MB RAM; 2 MB video RAM; 8-speed CD-ROM drive; 256 colors (recommended, 24-bit true color); QuickTime 2.1 or higher; Sound Blaster or compatible card.
Keywords: Art, Philippines -- Interactive multimedia; Art, Philippines -- Encyclopedias and dictionaries -- Interactive multimedia; Ethnology -- Philippines -- Interactive multimedia; Minorities -- Philippines -- Interactive multimedia